Paisaje y Educación Ambiental. - Otero Pastor, Isabel (Observatorio Medioambiental, 2000)
In the article, after a brief introduction about the meaning of Environmental Education and its parallel evolution to the relationships between man and nature, it's tried to explain the current necessity and the opportunity of the Environmental Education. Next, it's analysed how the study of the landscape helps to understand the idea of Environmental Education, going through the different views in the study of the landscape and its use for the Environmental Education. After all, it's pretended to stand out that the use of the landscape as the main reference in Environmental Education programs, has great didactic advantages because it's a tool that motivates and stimulates the senses. It's a realist and concrete instrument, which conceals mysteries, worldwide understood and useful for the classification of attitudes and for the implication in the action. 1.